Contribution of swimsuits to swimmer's performance - Moria, H.; Chowdhury, H.; Alam, F.; Subic, A.; Smits, A. J.; Jassim, R.; Bajaba, N. S. (Procedia Engineering, 2010)
Swimsuit is believed to play an important role in swimmer's performance. In competitive swimming (national, world and Olympic events) it is usually a very short winning time margins that often requires the help of advanced technology to determine the time difference between the winner and loser. Almost over 90% of swimmer's energy is spent to overcome hydrodynamic resistance during forward motion. Hence, the swimsuits might play an important role in reducing the hydrodynamic resistance and its associated energy loss during the swimming and can contribute positively to the final outcome. Development of efficient swimsuits is an on going process and the performance of swimsuit is believed to be getting better progressively. Currently, swimsuit manufacturers spend huge resources to design swimsuits using new materials and techniques. Very often swimsuit manufacturers claim and counterclaim about the performance of the swimsuits. However, there is no independent study that can verify these claims and counter claims. This paper describes a hydrodynamics comparative evaluation of two commercially available swimsuits and their role that might be played in swimsuit aerodynamics.